Notes on the underground: monetary policy in resource-rich economies - Ferrero, A; Seneca, M (Wiley, 2018)
The central bank of a commodity‐exporting small open economy faces the traditional trade‐off between domestic inflation and output gap. The commodity sector introduces a terms‐of‐trade inefficiency that gives rise to an endogenous cost‐push shock, changes the target level for output, reduces the slope of the Phillips curve, and increases the importance of stabilizing the output gap. Optimal monetary policy calls for a reduction of the interest rate following a drop in the oil price. In contrast, a central bank with a mandate to stabilize consumer price inflation raises interest rates to limit the inflationary impact of an exchange rate depreciation.